Phenomenon of Sound Synesthesia in the Development of Students’ Creative Thinking - Yunosova, Valentyna; Alekseeva, Larysa; Нlazova, Svitlana; Kornienko, Svitlana; Shkola, Galyna (Journal of History Culture and Art Research, 2020)
Changes in social, political and economic life, which have taken place very rapidly in recent years, are causing radical changes in various social spheres, in particular in higher education, the priority of which is the development of human subjective qualities that allow living in a changing world, changing oneself in it. In the modern educational paradigm, focused on meeting the needs of the individual, a special place is occupied by the problems of self-development, self-realization of a student. Therefore, it is advisable to use the phenomenon of synesthesia in the educational process. Today, the study of the phenomenon of synesthesia allows identifying the characteristics, to explain its potential in the development of human creativity. The relevance of the theory, methodology, and genesis of synesthesia is confirmed by changes in science itself, which again addressed the problem of person. The burst of research attention to the problem of synesthesia is due to the desire to find out the general principles of different ways of obtaining knowledge about the world, the desire to understand why such values can be realized in verbal, graphic, musical forms, awareness of the holistic nature of human thinking, which ultimately forms aesthetic worldview in representatives of different national and ethnic communities. One of the priority areas for the development of modern linguistics is the analysis of the sound organization of the text. In the framework of the proposed article, we focus on understanding the problem of the phenomenon of sound synesthesia in the creative thinking of students, which is a kind of additional mechanism for the perception and development of skills and abilities to analyze the sound and color relations in poetic text. The system-activity approach was applied in the work, which ensured the integrity, complexity, structure, and purposefulness of the research. With the help of appropriate methods synesthesia representations can be developed and used in the processes of learning and self-education, in learning foreign languages, creative activities and to compensate for disorders in sensory systems in people with psychophysical disorders. As a result of the study, it was found that the symbolism of sounds supports the semantic core of the meaning of language signs. Accordingly, sound synesthesia in the development of creative thinking of students will help to respond more quickly to the rapid changes taking place in the modern world.